Biomarkers of Dietary Exposure Are Associated with Lower Risk of Breast Fibroadenomas in Chinese Women - Dijkstra, S. Coosje (American Society for Nutrition, 2010)
Fibroadenomas are the most common benign breast condition among women and account for up to 50% of all breast biopsies being performed. Although considered a benign condition, fibroadenomas utilize substantial resources for management and treatment to rule out potential malignancies. Dietary factors may influence benign fibrocystic breast conditions, but little is known of their association with fibroadenomas. We examined possible associations between a broad spectrum of circulating biomarkers of dietary intake and risk of fibroadenomas. Participants were women in a breast self-examination trial in Shanghai, China who were diagnosed with fibroadenomas (n = 258) and 1035 controls. Conditional logistic regression was used to estimate adjusted odds ratios (OR) and 95% CI. Isoflavone concentrations were inversely associated with risk of fibroadenomas. Adjusted OR (95% CI) for the highest versus the lowest quartile of plasma concentration were 0.36 (0.16–0.79; P-trend < 0.001) for daidzein and 0.39 (0.19–0.84; P-trend = 0.010) for genistein. We also observed inverse associations between higher percentages of the RBC (n-3) fatty acids, eicosapentaenoic acid (EPA) ([0.38 (0.19–0.77); P-trend = 0.007] and docosapentaenoic acid (DPA) [0.32 (0.15–0.70); P-trend = 0.024], and fibroadenoma risk. Circulating concentrations of carotenoids, vitamin C, retinol, and ferritin were not associated with fibroadenoma risk. The inverse associations between plasma isoflavone concentrations and RBC EPA and DPA and fibroadenoma risk suggest that higher intakes of soy foods and fatty fish may lower the risk of fibroadenomas.